Comparison of Intravenous versus Intramuscular Administration of Corticotropin‐Releasing Hormone in Healthy Cats. (10th March 2013) - Eiler, K.C.; Bruyette, D.S.; Behrend, E.N.; Kemppainen, R.J.; Kass, P.H.
<x xml:space="preserve">Abstract</x> Background Because of the lack of a current validated assay for feline endogenous adrenocorticotropic hormone (ACTH) in response to administration of currently available ovine corticotropin‐releasing hormone (oCRH) preparations, a complete evaluation of the hypothalamic‐pituitary‐adrenal axis in cats has not been possible. Objective This study was undertaken to (1) determine the pituitary (ACTH) and adrenal (cortisol) response to both IV and IM administration of a currently available oCRH product in healthy cats, and (2) validate an endogenous ACTH assay for use in cats. Animals Seventeen healthy cats receiving oCRH (n = 11) or placebo (n = 6). Methods Prospective, randomized, placebo‐controlled study. oCRH at 1 μg/kg or placebo was given either IM or IV. Endogenous cortisol and ACTH concentrations were evaluated after the injection. A comparison of IM versus IV and placebo versus treatment was made. Results The DiaSorin immunoradiometric assay (IRMA) assay for ACTH performed well, showing both parallelism and acceptable intra‐ and interassay coefficients of variation. There was a significant difference between groups (P = .025) and a significant difference between times (P = .025) when endogenous ACTH concentrations were compared after oCRH IV or IM. No significant differences were observed in cortisol concentrations comparing IV to IM oCRH. Conclusions IM administration of oCRH results in significantly greater ACTH concentrations but not cortisol concentrations when compared with IV administration. Samples should be drawn before and at 60 minutes after the injection. The Diasorin IRMA is valid for feline endogenous ACTH measurements.